2005
DOI: 10.1007/s00595-005-2996-5
|View full text |Cite
|
Sign up to set email alerts
|

Management of Recurrent Malignant Pleural Effusion with Chemical Pleurodesis

Abstract: Talc resulted in the earliest expansion, minimal drainage, and the earliest tube and catheter removal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
2
23
1
Order By: Relevance
“…Prognosis following detection of MPE is generally poor, with reported median survivals of 3 (lung cancer) to 12 (breast cancer) months (5,7), and 1-month mortality rates ranging from 29% to 54% (24,25). In this study, the median survival from date of MP was 5.2 months, while the 1-month mortality rate of 19% was lower than in previous studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Prognosis following detection of MPE is generally poor, with reported median survivals of 3 (lung cancer) to 12 (breast cancer) months (5,7), and 1-month mortality rates ranging from 29% to 54% (24,25). In this study, the median survival from date of MP was 5.2 months, while the 1-month mortality rate of 19% was lower than in previous studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Talc has been reported as safe and efficacious for pleurodesis [15][16][17][18][19][20][21][22][23]. A Cochrane review reported that pleurodesis with talc provided the highest relative chance of MPE nonrecurrence when compared with bleomycin, tetracycline, mustine or chest-tube drainage alone [24].…”
Section: Discussionmentioning
confidence: 99%
“…First, the number of cases was relatively small; therefore, further studies with more patients are needed. Second, there was possible bias due to the different CT methods used (i.e., use agement of malignant pericardial effusion has not yet been established [17,18], identification and prompt control of malignant pericardial effusion can dramatically alleviate symptoms, allowing continued systemic therapy and improvement of survival from an otherwise controllable disease [19].…”
Section: Ct Of Pericardial Effusionmentioning
confidence: 99%